2020
DOI: 10.1029/2019tc006029
|View full text |Cite
|
Sign up to set email alerts
|

Active Thrusting in an Intermontane Basin: The Kumysh Fault, Eastern Tian Shan

Abstract: Faulting and folding on the margins of intermontane basins play important roles in accommodating the Cenozoic deformation of the Tian Shan, an intracontinental orogen in central Asia. In the eastern Tian Shan, the southern margin of the elongated Kumysh Basin is bounded by a NE dipping thrust fault, the Kumysh Fault. We report the first investigation of the slip rate of this fault, which is constrained at two sites by profiling the faulted topography and dating the abandoned alluvial fan surfaces. We obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Many studies e.g., Deng et al (2000), Thompson et al (2002), Shen et al (2003), Hubert-Ferrari et al (2007), Yang et al (2008), Lu et al (2019) have been conducted in the Western Tian Shan region to reveal the kinematics and deformation rate of fault-related folding and have shown that shortening is relatively uniformly distributed across the major intermontane basin boundaries and basin interior structures along a N-S transect of the Western Tian Shan, rather than solely at its margins. The Eastern Chinese Tian Shan is also dominated by intense tectonic deformation, which is shown by the study results of widespread active faults Deng et al (2000), Lin et al (2002), Wu et al (2016), Huang et al (2018a), Huang et al (2018b), Ren et al (2019), Wang et al (2020a), paleoearthquake ruptures Feng (1997) and global positioning system (GPS) measurements (Zhang et al, 2004;Yang et al, 2008;Wang and Shen, 2020). However, in contrast to the Western Tian Shan, the deformation pattern and slip partitioning in the Eastern Chinese Tian Shan remain unclear because of the lack of quantitative study on the deformation rate and kinematics of the major structural belt.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Many studies e.g., Deng et al (2000), Thompson et al (2002), Shen et al (2003), Hubert-Ferrari et al (2007), Yang et al (2008), Lu et al (2019) have been conducted in the Western Tian Shan region to reveal the kinematics and deformation rate of fault-related folding and have shown that shortening is relatively uniformly distributed across the major intermontane basin boundaries and basin interior structures along a N-S transect of the Western Tian Shan, rather than solely at its margins. The Eastern Chinese Tian Shan is also dominated by intense tectonic deformation, which is shown by the study results of widespread active faults Deng et al (2000), Lin et al (2002), Wu et al (2016), Huang et al (2018a), Huang et al (2018b), Ren et al (2019), Wang et al (2020a), paleoearthquake ruptures Feng (1997) and global positioning system (GPS) measurements (Zhang et al, 2004;Yang et al, 2008;Wang and Shen, 2020). However, in contrast to the Western Tian Shan, the deformation pattern and slip partitioning in the Eastern Chinese Tian Shan remain unclear because of the lack of quantitative study on the deformation rate and kinematics of the major structural belt.…”
Section: Introductionmentioning
confidence: 85%
“…The Eastern Chinese Tian Shan consists of the Bogda and Kuruktag ranges and several intermontane basins, such as the Turpan, Yanqi and Kumysh Basins (Figure 1B). Previous field investigations have recognized a series of active faults that bound the intermontane basins and accommodate N-S convergence (Deng et al, 2000;Lin et al, 2002;Fu et al, 2003;Wu et al, 2016;Wang et al, 2020a). The Eastern Chinese Tian Shan can be divided into two parts based on the Turpan basin (the largest intermontane basin).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…interior of the range [12][13][14], which is mainly distributed along the thrust structures with late Quaternary slip rates of 0.1-3 mm/yr in the western Tian Shan [13].…”
mentioning
confidence: 99%